2019
DOI: 10.1088/1361-6455/ab0e43
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed short-trajectory near-threshold harmonics as a sign of tunnel exit

Abstract: We study high-order harmonic generation (HHG) from atoms with different ionization potentials by solving numerically the time-dependent Schrödinger equation. A numerical scheme is used which allows us to resolve the contributions of only the short electron trajectory to HHG. With increasing laser wavelengths and reducing laser intensities, the calculated short-trajectory HHG spectra show an energy region near the threshold, where the HHG yields are suppressed strikingly. The width of the region depends on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…For smaller return energy corresponding to harmonics near the threshold, the differences between TDSE and MSFA predictions are somewhat more remarkable. It has been shown that near-threshold harmonics have complex origins beyond the description of quantum-trajectory theory [39]. For comparison, in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For smaller return energy corresponding to harmonics near the threshold, the differences between TDSE and MSFA predictions are somewhat more remarkable. It has been shown that near-threshold harmonics have complex origins beyond the description of quantum-trajectory theory [39]. For comparison, in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…predictions are somewhat more remarkable. It has been shown that near-threshold harmonics have complex origins beyond the description of quantum-trajectory theory [46]. For comparison, in figure 3(c), we also plot the predictions of MSFA with a short-range Coulomb potential.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, R − L is generally much larger than the maximal displacement of the electron in the driving field. Moreover, in our study, such a computational trick can also be used to help explore the mechanism of below-and near-threshold harmonic generation, as one can separate the contributions of trajectories evolving closely around the core from others by setting the absorbing area at proper spatial positions [47,48], as discussed in detail in section 4.2. Finally, the harmonic spectrum is obtained by the Fourier transform of the time-dependent dipole acceleration…”
Section: G(x Y) = G(x)g(y)mentioning
confidence: 99%